Impact of demographic and clinical parameters on video capsule transit time. Issue 10 (October 2016) - Niv, Eva; Pinchasovich, Hadassa; Yanai, Henit
Abstract : Background: Small bowel (SB) capsule endoscopy (CE) studies provide data on both gastric and SB transit times (GTT and SBTT, respectively). Aims: This study aimed to evaluate the influence of demographic and clinical parameters on the GTT and SBTT. Transit times for two generations of capsules (Pillcam SB2 and SB3) were also compared. Methods: Consecutive adult patients undergoing CE were included. GTT, SBTT, and cecum arrival rates were calculated and correlated to demographics and clinical characteristics. Results: A total of 332 CE studies were analyzed. Neither GTT nor SBTT were impacted by age or sex. SBTT was prolonged in newly diagnosed Crohn's disease (CD) patients compared with all other patients (303.1±90.3 vs. 243.6±83.6 min, P =0.02 for SB2, 267.8±63 vs. 228.6±72.3, P =0.01 for SB3, respectively). Moreover, CD patients had higher incomplete study rates compared with patients with all other diagnoses (29.4 vs. 7.3%, respectively, P =0.0116) in the SB2 subgroup. Higher cecum arrival rates were achieved by the SB3 capsule compared with SB2 (97 vs. 91%, P =0.04). Patients with prolonged gastric time or patients with incomplete studies had similar demographic and clinical characteristics as others. Conclusion: Age and sex apparently do not influence intestinal kinetics. Newly diagnosed CD patients have relatively prolonged SBTTs. Demographic and clinical parameters cannot predict prolonged GTT or cecum nonarrival.